Anti-disturbance micro-expansion lightweight ultra-high performance concrete and preparation method thereof

By using anti-disturbance micro-expansion lightweight ultra-high performance concrete in bridge maintenance and reinforcement and widening projects, the problem of difficult coexistence of traditional concrete in bridge maintenance and reinforcement and widening projects is solved, and the self-weight of concrete is achieved. Light, high disturbance resistance and excellent volume stability.

CN119430759AActive Publication Date: 2025-02-14WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411568647.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The prior art is difficult to meet the high disturbance and high flow performance of concrete during the bridge maintenance, reinforcement and widening process. Due to its large size and self-weight, traditional concrete is difficult to meet the requirements of repair, reinforcement and widening projects.

Method used

A lightweight ultra-high performance concrete that is anti-disturbing micro-expansion is used, and its formula includes cement, fly ash microbeads, silica fume, whiskers, nanocellulose, spherical gangue ceratops, gravel gangue ceratops, expansion Agents, shrink-scoring fibers, steel fibers and water-reducing agents, improve the concrete resistance by optimizing the proportion of gelling materials and the particle-shaped grading of high-performance coal gangue ceramics. Disturbance performance and volume stability.

Benefits of technology

It realizes the light self-weight, high disturbance resistance and excellent volume stability of concrete, and solves the problem that traditional concrete is difficult to coexist in bridge maintenance and reinforcement and widening projects, and is suitable for repairing and reinforcing and strengthening of uninterrupted traffic. and widening engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention provides anti-disturbance micro-expansion lightweight ultra-high performance concrete and a preparation method thereof. According to the concrete disclosed by the invention, the generation of micro cracks under disturbance can be effectively inhibited through the fiber bridging effect of the crystal whiskers and the temperature-shrinkage indented fibers and the micro pre-compressive stress of the temperature-shrinkage indented fibers under hydration exothermic excitation; the micro-crack healing effect of the nano-cellulose and the internal curing effect of the saturated pre-wetted coal gangue ceramsite cooperate to repair microstructure damage generated under strong disturbance, and the disturbance resistance of the concrete is further improved. The internal curing effect of the saturated pre-wetted coal gangue ceramsite and the expansion agent shrinkage compensation synergistically improve the volume stability of the concrete. The 28d compressive strength of the concrete is gt; compared with common ultra-high performance concrete, the volume weight of the ultra-high performance concrete is reduced by more than 20%, the anti-disturbance strength retention rate of the ultra-high performance concrete is greater than or equal to 95%, the ultra-high performance concrete shows excellent bonding and durability, the comprehensive performance of the ultra-high performance concrete is greatly improved, and the ultra-high performance concrete has important practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an anti-disturbance micro-expansion lightweight ultra-high performance concrete and a preparation method thereof. Background Art

[0002] With the increasing complexity of the national transportation network and the acceleration of urbanization, bridges, as key nodes of transportation infrastructure, are under unprecedented pressure. Many bridges are in urgent need of repair, reinforcement and widening due to disrepair, traffic overload and other reasons. Bridges are usually important transportation hubs. Once they are discontinued, they may have a huge impact on urban transportation and even the regional economy. Therefore, when repairing, reinforcing and widening bridges, traffic is usually not interrupted. Ensuring the continuity of traffic flow and the stability of service levels is the primary goal of engineering construction. The construction method of not interrupting traffic places higher demands on the performance of fresh concrete: (1) Due to the dense arrangement of steel bars in reinforcement or widening projects, the construction requires the slurry to have excellent flowability, but the key difficulty is the difficulty in balancing good working performance and high anti-disturbance performance; (2) Old bridges are usually close to or overloaded due to years of service or insufficient design load. Traditional concrete or ultra-high performance concrete is difficult to meet the requirements of repair, reinforcement and widening projects due to their large size and deadweight; (3) Due to the difference in volume stability between new and old concrete (the shrinkage of old concrete has stabilized, while that of newly poured concrete is still in the process of development), the shrinkage of newly poured concrete may cause the deterioration of the bonding interface between new and old concrete, thus placing higher demands on the volume stability of concrete. However, the current research on anti-disturbance concrete mainly focuses on the selection of cementitious materials for ordinary concrete or rapid-hardening concrete, the regulation of admixtures, and the construction process, and mainly focuses on improving the rapid-hardening and early-strengthening properties of concrete to improve its anti-disturbance performance. However, in large-scale repair, reinforcement, and widening projects, a long construction operation time and good anti-disturbance performance are required. There is currently no research on anti-disturbance lightweight ultra-high performance concrete. Therefore, it is urgent to develop an anti-disturbance micro-expansion lightweight ultra-high performance concrete to provide a more efficient, reliable, and durable solution for the maintenance, renovation, and upgrading of old bridges. Summary of the invention

[0003] In view of this, the present invention proposes an anti-disturbance micro-expansion lightweight ultra-high performance concrete and a preparation method thereof to solve or partially solve the problems existing in the prior art.

[0004] In the first aspect, the present invention provides an anti-disturbance micro-expansion lightweight ultra-high performance concrete, comprising the following raw materials in parts by weight: 35-40 parts of cement, 5-7 parts of fly ash beads, 6-9 parts of silica fume, 0.9-1.5 parts of whiskers, 0.05-0.10 parts of nanocellulose, 18-25 parts of spherical coal gangue ceramsite, 5-10 parts of crushed coal gangue ceramsite, 2.2-3.3 parts of expansion agent, 0.04-0.09 parts of temperature shrinkage notched fiber, 6.0-6.8 parts of steel fiber, 1.1-1.5 parts of water reducer, and 7.0-9.2 parts of water.

[0005] Preferably, the fly ash microbeads have a loss on ignition of ≤3.0%, a water requirement ratio of ≤90%, and a spherical particle volume ratio of ≥95%.

[0006] Preferably, the silica fume has a SiO2 mass content of ≥95% and a specific surface area of ​​≥19500m 2 / kg, 28d activity index ≥100%.

[0007] Preferably, the spherical gangue ceramsite and the crushed stone gangue ceramsite are continuously graded in the range of 0.075 to 4.75 mm; the fineness modulus of the spherical gangue ceramsite and the crushed stone gangue ceramsite is 3.1 to 3.7, the cylinder pressure strength is ≥12.0 MPa, and the bulk density is 700 to 900 kg / m 3 , apparent density is 1500~1700kg / m 3 , saturated surface dry water absorption rate is 12.0%~14.0%.

[0008] Preferably, the whisker is one of silicon carbide whisker, calcium sulfate whisker and calcium carbonate whisker;

[0009] The whisker has a diameter of 0.1 to 2 μm, a length of 10 to 30 μm, and a specific surface area of ​​20 to 80 m 2 / kg.

[0010] Preferably, the nanocellulose is cellulose nanofiber;

[0011] The cellulose nanofibers are 1 to 10 μm long, 10 to 60 nm in diameter, and have a specific surface area of ​​100 to 130 m 2 / kg.

[0012] Preferably, the water reducer is a polycarboxylate-based high-efficiency water reducer.

[0013] Preferably, the expansion agent is a high-performance expansion agent suitable for low water-binder ratio concrete, with a specific surface area of ​​≥250m 2 / kg, 7d expansion rate limited to ≥0.035%.

[0014] Preferably, the shrinkage rate of the temperature-shrinkage notched fiber is 0.5-12%, the response temperature is 30-100° C., the tensile strength is 500-1500 MPa, and the elastic modulus is 7-30 GPa.

[0015] In a second aspect, the present invention further provides a method for preparing the anti-disturbance micro-expansion lightweight ultra-high performance concrete, characterized in that it comprises the following steps:

[0016] S1. Mix 18 to 25 parts by weight of spherical gangue ceramsite and 5 to 10 parts by weight of crushed stone-shaped gangue ceramsite to obtain gangue ceramsite; add water to the gangue ceramsite, stir evenly to make the gangue ceramsite fully pre-wet, cover and place in a cool and dry place to stand, and obtain saturated pre-wetted gangue ceramsite; wherein the mass of water is 12 to 14% of the mass of the gangue ceramsite;

[0017] S2, pouring 35-40 parts by weight of cement, 6-9 parts of silica fume, 5-7 parts of fly ash microspheres, 2.2-3.3 parts of expansion agent, and 0.9-1.5 parts of whisker into a mixer and mixing to obtain a premix;

[0018] S3, pouring the saturated pre-wetted coal gangue ceramsite in S1 into the premix, stirring to obtain a mixture;

[0019] S4, adding 0.05-0.10 parts by weight of nanocellulose and 1.1-1.5 parts of a water reducing agent to 7.0-9.2 parts of water, stirring evenly, pouring into the mixture of S3, and stirring to obtain a mixed slurry;

[0020] S5. 6.0 to 6.8 parts by weight of steel fiber and 0.04 to 0.09 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, and molded after stirring. After covering with a film and curing, the mold is removed, and then standard curing or steam curing is performed to obtain the disturbance-resistant micro-expansion lightweight ultra-high performance concrete.

[0021] The anti-disturbance micro-expansion lightweight ultra-high performance concrete and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0022] 1. The disturbance-resistant micro-expansion lightweight ultra-high performance concrete prepared by the present invention has the characteristics of light weight, high disturbance resistance and excellent volume stability, etc., which effectively solves the problems of heavy concrete weight and difficulty in coexistence of high disturbance resistance and high flow performance in the current projects of repair, reinforcement and widening of old bridges without interrupting traffic. At the same time, it has a reasonable operable construction time and excellent comprehensive performance, which is of great significance to large-scale repair, reinforcement and widening projects without interrupting traffic; the two types of coal gangue light aggregates used can not only optimize the viscosity of the concrete slurry and reduce the dead weight, but also it is based on the solid waste coal gangue roasted with biomass fuel, has high mechanical properties and excellent water storage and release effects, is conducive to the resource utilization of coal gangue, and can provide excellent internal maintenance effect, effectively reduce the self-shrinkage of ultra-high performance concrete and improve the performance of the interface transition zone between the light aggregate and the matrix. At the same time, the present invention uses saturated pre-wetted coal gangue ceramsite during the preparation process, and the internal curing of the saturated pre-wetted coal gangue ceramsite and the shrinkage compensation of the expansion agent synergistically improve the volume stability of the ultra-high performance concrete. Therefore, the anti-disturbance micro-expansion lightweight ultra-high performance concrete prepared by the present invention has good resistance to vibrations generated by old bridges in projects such as repair, reinforcement and widening without interrupting traffic.

[0023] 2. The anti-disturbance micro-expansion lightweight ultra-high performance concrete of the present invention, the addition of whiskers, temperature shrinkage notched fibers and nanocellulose can improve the anti-disturbance performance of concrete during vehicle load disturbance and after strong disturbance, respectively. The fiber bridging effect of whiskers and temperature shrinkage notched fibers can effectively inhibit the generation of microcracks in concrete under the disturbance during coagulation and hardening, and the temperature shrinkage notched fibers can shrink under the excitation of hydration heat, which can produce micro pre-compression stress on the surrounding concrete matrix, which can further resist the disturbance. At the same time, the micro-crack healing effect of nanocellulose and the internal curing effect of saturated pre-wetted coal gangue lightweight aggregate can synergistically repair the microstructural damage caused by strong disturbance, thereby enhancing the anti-disturbance performance of concrete. In addition, temperature shrinkage notched fibers and steel fibers can synergistically enhance the toughness of concrete, thereby improving the fatigue resistance of concrete pavement during service, which is of great significance for improving the service life of concrete bridge structures. The bulk density of the anti-disturbance micro-expansion lightweight ultra-high performance concrete obtained by the present invention is <2050kg / m 3 At the same time, the 28d compressive strength is >120MPa, the 56d expansion rate is ≤100με, which is about 20% lower than the current ultra-high performance concrete. The anti-disturbance strength retention rate is ≥95%, and it shows excellent bonding and durability. The comprehensive performance has been greatly improved, which has important practical application value for maintenance, reinforcement and widening projects without interrupting traffic. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0026] The embodiment of the present application provides an anti-disturbance micro-expansion lightweight ultra-high performance concrete, comprising the following raw materials in parts by weight: 35-40 parts of cement, 5-7 parts of fly ash microspheres, 6-9 parts of silica fume, 0.9-1.5 parts of whiskers, 0.05-0.10 parts of nanocellulose, 18-25 parts of spherical coal gangue ceramsite, 5-10 parts of crushed coal gangue ceramsite, 2.2-3.3 parts of expansion agent, 0.04-0.09 parts of temperature shrinkage notched fiber, 6.0-6.8 parts of steel fiber, 1.1-1.5 parts of water reducer, and 7.0-9.2 parts of water.

[0027] The anti-disturbance micro-expansion lightweight ultra-high performance concrete of the present invention adopts whiskers and nanocellulose to prepare highly anti-disturbance lightweight ultra-high performance concrete. On the one hand, the anti-disturbance performance of the lightweight ultra-high performance concrete is enhanced by changing the grading of coal gangue light aggregate to adjust the slurry viscosity and adding nanofiber particles such as whiskers and nanocellulose. On the other hand, the volume stability of the lightweight ultra-high performance concrete is regulated by the internal curing effect of saturated pre-wetted light aggregate and the shrinkage compensation of the expansion agent. At the same time, the addition of light aggregate can not only reduce the dead weight of the ultra-high performance concrete, but also the internal curing effect of the light aggregate releasing water can enhance the anti-disturbance effect of the concrete, thereby achieving high fluidity, anti-disturbance and micro-expansion of the lightweight ultra-high performance concrete.

[0028] In some embodiments, the cement is PO 52.5 cement, which is a commercially available material.

[0029] In some embodiments, the fly ash microbeads have a loss on ignition of ≤3.0%, a water demand ratio of ≤90%, and a spherical particle volume fraction of ≥95%.

[0030] In some embodiments, the silica fume has a SiO2 mass content of ≥95% and a specific surface area of ​​≥19500 m 2 / kg, 28d activity index ≥100%.

[0031] In some embodiments, the spherical coal gangue ceramsite and the crushed stone coal gangue ceramsite are continuously graded from 0.075 to 4.75 mm;

[0032] The fineness modulus of spherical gangue ceramsite and crushed stone gangue ceramsite is 3.1~3.7, the cylinder pressure strength is ≥12.0MPa, and the bulk density is 700~900kg / m 3 , apparent density 1500~1700kg / m 3 , saturated surface dry water absorption rate is 12.0%~14.0%.

[0033] Specifically, in the present invention, the crushed stone-shaped coal gangue ceramsite is a coal gangue ceramsite in any shape except spherical coal gangue ceramsite.

[0034] In some embodiments, the whisker is one of silicon carbide whisker, calcium sulfate whisker and calcium carbonate whisker; preferably, the whisker is silicon carbide whisker;

[0035] The whisker diameter is 0.1-2 μm, the length is 10-30 μm, and the specific surface area is 20-80 m 2 / kg.

[0036] In some embodiments, the nanocellulose is cellulose nanofibers;

[0037] The length of cellulose nanofibers is 1-10 μm, the diameter is 10-60 nm, and the specific surface area is 100-130 m 2 / kg.

[0038] The nanocellulose used in this application has a high comparative area and high cellulose content. On the one hand, the hydrophilic nanocellulose can induce the growth of calcium silicate hydrate (CSH gel), form a bridge structure between the hydration products, optimize the pore size distribution and pore structure of the concrete, and improve the structural density; on the other hand, the fiber can form a network structure in the microcracks to prevent the cracks from expanding, and under the condition of light aggregate water release and internal curing, the fiber can further promote the hydration of unhydrated cement and fill the microcracks. The above performance is of great significance for the anti-disturbance performance of concrete; and nanocellulose comes from plant fibers (such as wood, agricultural waste, etc.), belongs to renewable resources, and has a wide range of sources, reducing carbon emissions. At the same time, the silicon carbide whiskers used in this study have a large aspect ratio, high specific surface area and high modulus, which can effectively disperse the applied stress evenly to various areas of the concrete, reduce local damage caused by stress concentration, and have good interface bonding properties with hydration products such as CSH gel, further enhancing the anti-disturbance performance of lightweight ultra-high performance concrete. In addition, at the macroscopic scale, the temperature-shrinkage notched fibers can shrink under the stimulation of hydration exotherm, thereby generating micro-precompressive stress on the surrounding concrete matrix, which can further resist disturbance.

[0039] In some embodiments, the water reducing agent is a polycarboxylate-based high-efficiency water reducing agent, and the solid content is ≥30%.

[0040] In some embodiments, the expansion agent is a high-performance expansion agent suitable for low water-binder ratio concrete, with a specific surface area of ​​250 m 2 / kg, 7d expansion rate limited to ≥0.035%.

[0041] In some embodiments, the shrinkage rate of the temperature-shrinkage scored fiber is 0.5-12%, the response temperature is 30-100° C., the tensile strength is 500-1500 MPa, and the elastic modulus is 7-30 GPa.

[0042] Specifically, the temperature-shrinkage scored fiber of the present invention has a specific preparation method comprising the following steps:

[0043] 1) Two extruders are used to extrude the heat shrinkable core material mixture and the heat shrinkable skin material mixture into a die head with two cavities, wherein the heat shrinkable skin material enters the cavity corresponding to the skin material, and the heat shrinkable core material enters the cavity corresponding to the core material. The materials in the two cavities converge at the position of the spinneret of the extruder, wherein the spinneret has an inner ring and an outer ring, the inner ring of the spinneret is connected to the cavity of the core material, and the outer ring of the spinneret is connected to the cavity of the skin material. The two molten materials are extruded (melt extrusion) through the spinneret, and stick together in the air, cooled by a cold water tank, and then drawn in hot water at 90 to 100° C. to form a composite fiber with a skin-core structure;

[0044] Among them, the raw materials and their mass percentages in the heat shrinkable leather material mixture are: 97.5% polyoxymethylene, 1.5% maleic anhydride grafted compatibilizer (provided by Dongguan Shenghao Plastic Raw Materials Co., Ltd., model PP-G-MAH) and 1% phthalate (plasticizer); the extrusion pressure of the leather material cavity is 8MPa, and the melting temperature is maintained at 250°C;

[0045] In the heat shrinkable core material mixture, the raw materials and their mass percentages are: polyester 98%, steel nucleating agent 2% (composed of dibenzylidene sorbitol and sodium benzoate in a mass ratio of 1:1); the extrusion pressure is 6MPa, and the melting temperature is maintained at 210°C;

[0046] After the skin material and the core material are combined, they are extruded through a spinneret. The extrusion temperature of the two molten materials is 220°C and the extrusion pressure is 7MPa.

[0047] The average diameter of the obtained core fiber is 0.15 mm, and the thickness of the skin fiber is 0.05 to 0.1 mm;

[0048] 2) adding the obtained composite fiber into octamethylcyclotetrasiloxane organosilicon solution for modification (time is 12 hours), and then indenting the surface after drying to increase the bonding performance with concrete paste;

[0049] 3) adding the obtained composite fiber to a modified polyvinyl alcohol solution with an expansion component added thereto for coating and modification (for 24 hours), taking it out and drying it to prepare a temperature-shrinkage notched fiber;

[0050] The modified polyvinyl alcohol solution is obtained by uniformly mixing a polyvinyl alcohol solution (5 wt %) and a liquid expansion agent in a mass ratio of 7:3 (1:0.43).

[0051] The water-soluble film on the surface of the temperature-shrinkage notched fiber obtained by the present invention dissolves and the expansion components can react with concrete to expand. The free expansion rate of the expansion agent in a closed environment is 0.02%. The bonding strength between the core-skin fiber and the concrete is greater than 20MPa. The shrinkage rate of the obtained composite fiber is 0.5-12%, the response temperature is 30-100°C, the tensile strength is 700MPa, and the elastic modulus is 15.0GPa.

[0052] In some embodiments, the water is ordinary tap water that meets the requirements of the "Standard for Water Use in Concrete" JGJ63.

[0053] The anti-disturbance micro-expansion lightweight ultra-high performance concrete of the present invention adjusts the slurry viscosity by rationally optimizing the proportion of cementitious materials and the particle shape and gradation of high-performance coal gangue ceramsite; improves the anti-disturbance performance of lightweight ultra-high performance concrete by using whiskers, temperature shrinkage notched fibers and nanocellulose; and synergistically improves the toughness of concrete and enhances the mechanical properties by using temperature shrinkage notched fibers and steel fibers. At the same time, the internal curing effect provided by the saturated pre-wetted coal gangue lightweight aggregate and the shrinkage compensation of the expansion agent synergistically improve the volume stability of the concrete. In addition, the coal gangue ceramsite used in the present invention is based on solid waste coal gangue calcined by biomass fuel, which is of great significance to the sustainable development of the environment. The bulk density of the anti-disturbance micro-expansion lightweight ultra-high performance concrete obtained by the present invention is ≤2050kg / m 3 , fluidity 530mm~670mm, 28d compressive strength ≥120MPa, 56d expansion rate ≤100με, anti-disturbance strength retention rate ≥95%, compared with the current ultra-high performance concrete density (about 2600kg / m 3 ) is reduced by more than 20%, effectively reducing the load on the original structure. At the same time, it has excellent volume stability and bonding properties, and the comprehensive performance is greatly improved. It has important practical application value for maintenance, reinforcement and widening projects without interrupting traffic.

[0054] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned anti-disturbance micro-expansion lightweight ultra-high performance concrete, comprising the following steps:

[0055] S1. Mix 18 to 25 parts by weight of spherical gangue ceramsite and 5 to 10 parts by weight of crushed stone-shaped gangue ceramsite to obtain gangue ceramsite; add water to the gangue ceramsite, stir evenly to make the gangue ceramsite fully pre-wet, cover and place in a cool and dry place to stand, and obtain saturated pre-wetted gangue ceramsite; wherein the mass of water is 12 to 14% of the mass of the gangue ceramsite;

[0056] S2, pouring 35-40 parts by weight of cement, 6-9 parts of silica fume, 5-7 parts of fly ash microspheres, 2.2-3.3 parts of expansion agent, and 0.9-1.5 parts of whisker into a mixer and mixing to obtain a premix;

[0057] S3, pouring the saturated pre-wetted coal gangue ceramsite in S1 into the premix, stirring to obtain a mixture;

[0058] S4, adding 0.05-0.10 parts by weight of nanocellulose and 1.1-1.5 parts of a water reducing agent to 7.0-9.2 parts of water, stirring evenly, pouring into the mixture of S3, and stirring to obtain a mixed slurry;

[0059] S5. 6.0 to 6.8 parts by weight of steel fiber and 0.04 to 0.09 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, and molded after stirring. After covering with a film and curing, the mold is removed, and then standard curing or steam curing is performed to obtain the disturbance-resistant micro-expansion lightweight ultra-high performance concrete.

[0060] In some embodiments, 18 to 25 parts by weight of spherical gangue ceramsite and 5 to 10 parts by weight of crushed stone-shaped gangue ceramsite are mixed in a suitable container to obtain gangue ceramsite; water is added to the gangue ceramsite, stirred several times to ensure the uniformity of aggregate pre-wetting, covered and placed in a cool and dry place to stand, to obtain saturated pre-wetted gangue ceramsite; wherein the mass of water is 12 to 14% of the mass of the gangue ceramsite (i.e., the water content is sufficient for saturated pre-wetting).

[0061] In some embodiments, 35 to 40 parts by weight of cement, 6 to 9 parts of silica fume, 5 to 7 parts of fly ash microspheres, 2.2 to 3.3 parts of expansion agent, and 0.9 to 1.5 parts of whisker are poured into a mixer and mixed at a speed of 35±2 r / min for 3 minutes to obtain a premix.

[0062] In some embodiments, the saturated pre-wetted coal gangue ceramsite in S1 is poured into the premix, and stirred at a rotation speed of 35±2 r / min for 3 minutes to obtain a mixture.

[0063] In some embodiments, 0.05 to 0.10 parts by weight of nanocellulose and 1.1 to 1.5 parts of a water reducer are added to 7.0 to 9.2 parts of water, stirred evenly, and then poured into the mixture of S3, and stirred at a speed of 35 ± 2 r / min for 5 minutes to obtain a mixed slurry;

[0064] In some embodiments, 6.0 to 6.8 parts by weight of steel fiber and 0.04 to 0.09 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, fully stirred at a speed of 35±2r / min for 4 minutes, loaded into a mold after stirring evenly, covered with a film and cured for 24 hours before demolding, and then standard curing or steam curing is carried out to obtain the anti-disturbance micro-expansion lightweight ultra-high performance concrete.

[0065] The disturbance-resistant micro-expansion lightweight ultra-high performance concrete prepared in this application has the characteristics of light weight, high disturbance resistance and excellent volume stability, which effectively solves the current problem that the heavy weight of concrete and the high disturbance resistance performance are difficult to coexist with high fluidity. At the same time, it has excellent comprehensive performance, which is of great significance for repair, reinforcement and widening projects without interrupting traffic. The raw material coal gangue light aggregate used is roasted by biomass fuel, which effectively reduces CO2 emissions in the production process, and absorbs a large amount of solid waste coal gangue, reducing the consumption of natural sand and gravel; this application uses whiskers and nanocellulose, which not only enhances its disturbance resistance through dense filling and fiber bridging during the disturbance process, but also the temperature shrinkage notched fiber can shrink under the stimulation of hydration heat release, thereby generating micro pre-compression stress on the surrounding concrete matrix, which can further resist disturbance. In addition, if the concrete is severely disturbed and damaged in the early stage, the present invention can further improve its anti-disturbance performance through the micro-crack healing effect of nanocellulose and the repair of micro-structure damage under the curing effect of light aggregate, which has an important guiding role in the research and development and preparation of anti-disturbance lightweight ultra-high performance concrete; the bulk density of the anti-disturbance micro-expansion lightweight ultra-high performance concrete obtained by the present invention is ≤2050kg / m 3 , fluidity 530mm~670mm, 28d compressive strength ≥120MPa, 56d expansion rate ≤100με, anti-disturbance strength retention rate ≥0.95, compared with the current common ultra-high performance concrete density (about 2600kg / m 3 ) is reduced by more than 20%, the anti-disturbance performance is greatly improved, and at the same time it has excellent bonding performance and durability, the comprehensive performance has been greatly improved, and it has important practical application value.

[0066] The following further illustrates the anti-disturbance micro-expansion lightweight ultra-high performance concrete and its preparation method of the present invention with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0067] The following tests simulated three different traffic conditions: light traffic load (amplitude 1 mm, frequency 3 Hz), medium traffic load (amplitude 2.5 mm, frequency 5 Hz) and heavy traffic load (amplitude 4 mm, frequency 8 Hz). The disturbance started from the completion of pouring and continued until the final setting time corresponding to each embodiment and comparative example. The working performance (setting time and fluidity) and mechanical properties (compression, bending, splitting tensile, bonding, etc.) of the specimens were tested respectively.

[0068] In the following examples and comparative examples, the cement is PO·52.5 cement, provided by Huaxin Cement Co., Ltd., with a specific surface area of ​​365m 2 / kg; fly ash microspheres were provided by Tianjin Zhucheng New Materials Co., Ltd., with a loss on ignition of 2.5% and a specific surface area of ​​1300m 2 / kg, 28d activity index ≥90%; silica fume provided by Shanghai Token Building Materials Co., Ltd., specific surface area 21500m 2 / kg; Silicon carbide whiskers were provided by Formans Technology Co., Ltd., with a diameter of 0.5-2 μm, a length of 10-20 μm, and an elastic modulus of 450-700 GPa; Nanocellulose was provided by Jinan Shengquan Group Co., Ltd., specifically Shengquan Group Nanocellulose, with a diameter of 10-60 nm and a length of 1-5 μm; spherical gangue ceramsite and crushed stone gangue ceramsite are provided by Huainan Dongchen Group Co., Ltd., both of which are 0.075-4.75 mm continuous grading, fineness modulus 3.1-3.7, cylinder pressure strength ≥12 MPa, and bulk density 700-800 kg / m 3 The expansion agent is provided by Wuhan Sanyuan Special Building Materials Co., Ltd., specifically HPS high-performance expansion clinker, with a specific surface area of ​​≥250m 2 / kg, 7d expansion rate limit ≥0.035%; the water reducer is a coagulant-type polycarboxylate-based high-efficiency water reducer produced by Jiangsu Subote New Materials Co., Ltd., with a solid content of 30%; the water is ordinary tap water.

[0069] In the following embodiments, the method for preparing the temperature-shrinkage scored fiber comprises the following steps:

[0070] 1) Two extruders are used to extrude the heat shrinkable core material mixture and the heat shrinkable skin material mixture into a die head with two cavities, wherein the heat shrinkable skin material enters the cavity corresponding to the skin material, and the heat shrinkable core material enters the cavity corresponding to the core material. The materials in the two cavities converge at the position of the spinneret of the extruder, wherein the spinneret has an inner ring and an outer ring, the inner ring of the spinneret is connected to the cavity of the core material, and the outer ring of the spinneret is connected to the cavity of the skin material. The two molten materials are extruded (melt extrusion) through the spinneret, and stick together in the air, cooled by a cold water tank, and then drawn in hot water at 90 to 100° C. to form a composite fiber with a skin-core structure;

[0071] Among them, the raw materials and their mass percentages in the heat shrinkable leather material mixture are: 97.5% polyoxymethylene, 1.5% maleic anhydride grafted compatibilizer (provided by Dongguan Shenghao Plastic Raw Materials Co., Ltd., model PP-G-MAH) and 1% phthalate (plasticizer); the extrusion pressure of the leather material cavity is 8MPa, and the melting temperature is maintained at 250°C;

[0072] In the heat shrinkable core material mixture, the raw materials and their mass percentages are: polyester 98%, steel nucleating agent 2% (composed of dibenzylidene sorbitol and sodium benzoate in a mass ratio of 1:1); the extrusion pressure is 6MPa, and the melting temperature is maintained at 210°C;

[0073] After the skin material and the core material are combined, they are extruded through a spinneret. The extrusion temperature of the two molten materials is 220°C and the extrusion pressure is 7MPa.

[0074] The average diameter of the obtained core fiber is 0.15 mm, and the thickness of the skin fiber is 0.05 to 0.1 mm;

[0075] 2) adding the obtained composite fiber into octamethylcyclotetrasiloxane organosilicon solution for modification (time is 12 hours), and then indenting the surface after drying to increase the bonding performance with concrete paste;

[0076] 3) adding the obtained composite fiber to a modified polyvinyl alcohol solution with an expansion component added thereto for coating and modification (for 24 hours), taking it out and drying it to prepare a temperature-shrinkage notched fiber;

[0077] The modified polyvinyl alcohol solution is obtained by uniformly mixing a polyvinyl alcohol solution (5 wt %) and a liquid expansion agent in a mass ratio of 7:3 (1:0.43).

[0078] Example 1

[0079] The embodiment of the present application provides an anti-disturbance micro-expansion lightweight ultra-high performance concrete, comprising the following raw materials in parts by weight: 39 parts of cement, 6 parts of fly ash microspheres, 8.6 parts of silica fume, 1.5 parts of silicon carbide whiskers, 0.09 parts of nanocellulose, 18 parts of spherical coal gangue ceramsite, 10 parts of crushed coal gangue ceramsite, 3.0 parts of expansion agent, 0.08 parts of temperature shrinkage notched fiber, 6.7 parts of steel fiber, 1.1 parts of polycarboxylic acid water reducer, and 7.3 parts of water.

[0080] The method for preparing the above-mentioned anti-disturbance micro-expansion lightweight ultra-high performance concrete comprises the following steps:

[0081] S1. Mix 18 parts by weight of spherical gangue ceramsite and 10 parts by weight of crushed stone gangue ceramsite to obtain gangue ceramsite; add water to the gangue ceramsite, stir to pre-wet the gangue ceramsite, cover and place in a cool and dry place to stand, and obtain saturated pre-wet gangue ceramsite; wherein the mass of water is 13% of the mass of the gangue ceramsite;

[0082] S2, pour 39 parts by weight of cement, 8.6 parts of silica fume, 6 parts of fly ash microspheres, 3.0 parts of expansion agent, and 1.5 parts of calcium carbonate whisker into a mixer and mix at a speed of 35±2r / min for 3 minutes to obtain a premix;

[0083] S3, pouring the saturated pre-wetted coal gangue ceramsite in S1 into the premix, stirring to obtain a mixture;

[0084] S4, adding 0.09 parts by weight of nanocellulose and 1.1 parts of polycarboxylate water-reducing agent to 7.3 parts of water, stirring evenly, pouring into the mixture of S3, stirring at a speed of 35±2r / min for 5min, to obtain a mixed slurry;

[0085] S5. 6.7 parts by weight of steel fiber and 0.08 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, and fully stirred at a speed of 35±2r / min for 4 minutes. After stirring evenly, the mixture is loaded into a mold, covered with a film and cured for 24 hours, and then the mold is removed. Then, standard curing is carried out (at a temperature of 20°C and a relative humidity of 98%RH for 28 days) to obtain the anti-disturbance micro-expansion lightweight ultra-high performance concrete.

[0086] Example 2

[0087] The embodiment of the present application provides an anti-disturbance micro-expansion lightweight ultra-high performance concrete, comprising the following raw materials in parts by weight: 37 parts of cement, 7 parts of fly ash microspheres, 7.8 parts of silica fume, 1.3 parts of silicon carbide whiskers, 0.08 parts of nanocellulose, 22 parts of spherical coal gangue ceramsite, 7.2 parts of crushed coal gangue ceramsite, 2.6 parts of expansion agent, 0.06 parts of temperature shrinkage notched fiber, 6.5 parts of steel fiber, 1.2 parts of polycarboxylic acid water reducer, and 8.0 parts of water.

[0088] The method for preparing the above-mentioned anti-disturbance micro-expansion lightweight ultra-high performance concrete comprises the following steps:

[0089] S1. Mix 22 parts by weight of spherical gangue ceramsite and 7.2 parts by weight of crushed stone-shaped gangue ceramsite to obtain gangue ceramsite; add water to the gangue ceramsite, stir to pre-wet the gangue ceramsite, cover and place in a cool and dry place to stand, and obtain saturated pre-wet gangue ceramsite; wherein the mass of water is 13% of the mass of the gangue ceramsite;

[0090] S2, pour 37 parts by weight of cement, 7.8 parts of silica fume, 7 parts of fly ash microspheres, 2.6 parts of expansion agent, and 1.3 parts of calcium carbonate whisker into a mixer and mix at a speed of 35±2r / min for 3 minutes to obtain a premix;

[0091] S3, pouring the saturated pre-wetted coal gangue ceramsite in S1 into the premix, stirring to obtain a mixture;

[0092] S4, adding 0.06 parts by weight of nanocellulose and 1.2 parts of polycarboxylate water-reducing agent to 8.0 parts of water, stirring evenly, pouring into the mixture of S3, stirring at a speed of 35±2r / min for 5min, to obtain a mixed slurry;

[0093] S5. 6.5 parts by weight of steel fiber and 0.06 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, and fully stirred at a speed of 35±2r / min for 4 minutes. After stirring evenly, the mixture is loaded into a mold, covered with a film and cured for 24 hours, and then the mold is removed. Then, standard curing is carried out (at a temperature of 20°C and a relative humidity of 98%RH for 28 days) to obtain the anti-disturbance micro-expansion lightweight ultra-high performance concrete.

[0094] Example 3

[0095] The embodiment of the present application provides an anti-disturbance micro-expansion lightweight ultra-high performance concrete, comprising the following raw materials in parts by weight: 36 parts of cement, 6 parts of fly ash microspheres, 7.0 parts of silica fume, 1.15 parts of silicon carbide whiskers, 0.07 parts of nanocellulose, 24 parts of spherical coal gangue ceramsite, 5.7 parts of crushed coal gangue ceramsite, 2.3 parts of expansion agent, 0.04 parts of temperature shrinkage notched fiber, 6.3 parts of steel fiber, 1.4 parts of polycarboxylic acid water reducer, and 8.8 parts of water.

[0096] The method for preparing the above-mentioned anti-disturbance micro-expansion lightweight ultra-high performance concrete comprises the following steps:

[0097] S1. Mix 24 parts by weight of spherical gangue ceramsite and 5.7 parts by weight of crushed stone-shaped gangue ceramsite to obtain gangue ceramsite; add water to the gangue ceramsite, stir to pre-wet the gangue ceramsite, cover and place in a cool and dry place to stand, and obtain saturated pre-wet gangue ceramsite; wherein the mass of water is 13% of the mass of the gangue ceramsite;

[0098] S2, pour 36 parts by weight of cement, 7.0 parts of silica fume, 6 parts of fly ash microspheres, 2.3 parts of expansion agent, and 1.15 parts of calcium carbonate whisker into a mixer and mix at a speed of 35±2r / min for 3min to obtain a premix;

[0099] S3, pouring the saturated pre-wetted coal gangue ceramsite in S1 into the premix, stirring to obtain a mixture;

[0100] S4, adding 0.07 parts by weight of nanocellulose and 1.4 parts of polycarboxylate water-reducing agent to 8.8 parts of water, stirring evenly, pouring into the mixture of S3, stirring at a speed of 35±2r / min for 5min, to obtain a mixed slurry;

[0101] S5. 6.3 parts by weight of steel fiber and 0.04 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, and fully stirred at a speed of 35±2r / min for 4 minutes. After stirring evenly, the mixture is loaded into a mold, covered with a film and cured for 24 hours, and then the mold is removed. Then, standard curing is carried out (at a temperature of 20°C and a relative humidity of 98%RH for 28 days) to obtain the anti-disturbance micro-expansion lightweight ultra-high performance concrete.

[0102] Comparative Example 1

[0103] This comparative example provides a commercially available C50 anti-disturbance concrete, comprising the following raw materials in parts by weight: 14 parts of cement, 4 parts of fly ash, 3.2 parts of mineral powder, 42.5 parts of crushed stone, 31.2 parts of river sand, 2.0 parts of polycarboxylate water reducer, and 6.1 parts of water.

[0104] The preparation method of the C50 disturbance-resistant concrete provided in the above comparative example comprises the following steps:

[0105] S1: Pour cement, fly ash, mineral powder, crushed stone and river sand into a mixer and mix them at a speed of 35 r / min for 3 minutes to obtain a premix;

[0106] S2: adding polycarboxylate water reducer and water to the premix obtained in S1, stirring the mixture at a speed of 35 r / min for 5 min to obtain C50 disturbance-resistant concrete.

[0107] Comparative Example 2

[0108] This comparative example provides a common UHPC material containing quartz sand, including the following raw materials in parts by weight: 33.2 parts of cement, 6.2 parts of fly ash microspheres, 7.0 parts of silica fume, 40.8 parts of quartz sand, 6.1 parts of steel fiber, 2.3 parts of expansion agent, 1.2 parts of polycarboxylate water reducer, and 7.2 parts of water.

[0109] The preparation method of the common UHPC material containing quartz sand provided in the above comparative example comprises the following steps:

[0110] S1: Pour cement, fly ash microbeads, silica fume and quartz sand into a mixer and mix them at a speed of 35 r / min for 3 minutes to obtain a premix;

[0111] S2: adding the polycarboxylate water-reducing agent, the swelling agent and water to the premix obtained in S1, and stirring the mixture at a speed of 35 r / min for 5 min to obtain a mixed slurry;

[0112] S3 uniformly adds the steel fiber into the mixed slurry obtained in S2, and fully stirs it at a speed of 35 r / min for 5 minutes to obtain a common UHPC material.

[0113] Comparative Example 3

[0114] This comparative example provides a lightweight ultra-high performance concrete containing shale lightweight aggregate (continuous grading of particle size 0.075-4.75 mm, water absorption rate 5.8%) with the same strength grade as the coal gangue material in Example 1, comprising the following raw materials in parts by weight: 37.0 parts of cement, 6.0 parts of fly ash microspheres, 7.0 parts of silica fume, 31.0 parts of crushed stone shale ceramsite, 6.3 parts of steel fiber, 2.5 parts of expansion agent, 1.4 parts of polycarboxylate water reducer, and 8.8 parts of water.

[0115] The method for preparing the lightweight ultra-high performance concrete provided in the above comparative example comprises the following steps:

[0116] S1, placing 31.0 parts by weight of crushed stone-shaped shale ceramsite in a nylon bag, soaking it in water for 24 hours, then taking it out and draining it to a saturated surface dry state to obtain pre-wet shale ceramsite;

[0117] S2, pouring 37.0 parts by weight of cement, 7.0 parts of silica fume, 6.0 parts of fly ash microspheres, 2.5 parts of expansion agent and the pre-wetted shale ceramsite obtained in S1 into a mixer and mixing at a speed of 35 r / min for 3 minutes to obtain a premix;

[0118] S3, adding 1.4 parts by weight of a polycarboxylate water-reducing agent and 8.8 parts of water into the premix obtained in S2, and stirring at a speed of 35 r / min for 5 min to obtain a mixed slurry;

[0119] S4. Add steel fiber to the mixed slurry in S3, stir it thoroughly at a speed of 35r / min for 4 minutes, put it into a mold after stirring evenly, cover it with a film and cure it for 24 hours to obtain ultra-high performance concrete containing shale expanded clay.

[0120] Performance Testing

[0121] The performance of the disturbance-resistant micro-expansion lightweight ultra-high performance concrete prepared in Examples 1 to 3 and the concrete in Comparative Examples 1 to 3 was tested, wherein the ratio of the strength after disturbance to the strength without disturbance was defined as the disturbance-resistant strength retention rate, and the test results are shown in Tables 1 to 3.

[0122] It can be seen from Table 1 that the anti-disturbance micro-expansion lightweight ultra-high performance concrete obtained by the present invention has the advantages of light weight, high strength, high anti-disturbance, and micro-expansion. As shown in Examples 1 to 3, the apparent density of the anti-disturbance micro-expansion lightweight ultra-high performance concrete obtained is ≤2050kg / m 3 , slump flowability 560-660mm, compressive strength up to 120MPa or more, and excellent bonding performance and bending and tensile performance. Compared with comparative examples 1-3, it can be seen that the anti-disturbance micro-expansion lightweight ultra-high performance concrete of the present invention has good volume stability and its own weight is significantly reduced.

[0123] Table 1 - Concrete properties of the examples and comparative examples in undisturbed state

[0124]

[0125] Table 2 - Concrete compressive strength of the embodiments and comparative examples under different disturbance conditions (MPa)

[0126]

[0127]

[0128] Note: The value in brackets is the ratio of the concrete strength at each age under different traffic load disturbances to the undisturbed concrete strength (i.e., anti-disturbance strength retention rate).

[0129] As shown in Table 2, under the disturbance of light traffic load, each embodiment and comparative example showed excellent anti-disturbance effect; however, under the action of medium traffic load, the embodiment still showed signs of enhancement at each age, while each comparative example gradually showed a decreasing trend. The reason for the above phenomenon is that the lightweight ultra-high performance concrete incorporating whiskers, temperature shrinkage notched fibers and nanocellulose has good anti-disturbance, and the optimization of the viscosity of the lightweight ultra-high performance concrete paste by spherical and crushed stone coal gangue ceramsite makes it more resistant to external disturbance. In addition, under the disturbance of heavy traffic load, the embodiment has microcrack damage to its internal structure due to severe disturbance, so its compressive strength retention rate is greatly reduced in the early stage (3h), but in the later stage, the microcrack healing effect of nanocellulose and the internal curing effect of saturated pre-wetted coal gangue light aggregate repair the damage of the microstructure, so the strength retention rate in the later stage (28d) is significantly improved, and the strength is only reduced by less than 3% compared with the undisturbed state. Different from the embodiment, the maximum strength retention rate of the comparative example under heavy traffic load disturbance is reduced by nearly 20%, so its strong disturbance resistance performance is poor. It is worth noting that although the ultra-high performance concrete still has a high strength (>120MPa) under heavy traffic load disturbance, its strength is significantly reduced (reduced by 17.0%) compared with the non-vibrated group, so its heavy traffic disturbance resistance performance is poor.

[0130] Table 3 - Concrete flexural tensile and bond strength (MPa) of the embodiments and comparative examples under different disturbance conditions

[0131]

[0132]

[0133] Note: The value in brackets is the ratio of concrete strength under different traffic load disturbances to the undisturbed concrete strength (i.e., anti-disturbance strength retention rate).

[0134] As shown in Table 3, the flexural tensile strength and bonding strength of each embodiment are relatively excellent under different degrees of traffic load (the minimum anti-disturbance strength retention rate is still >95%); while the flexural tensile and bonding properties of the comparative example are significantly reduced under medium and heavy traffic load disturbances (especially under heavy traffic loads, the flexural tensile strength is reduced by nearly 20% at most, and the bonding strength is reduced by nearly 30% at most); the above test results show that the anti-disturbance micro-expansion lightweight ultra-high performance concrete obtained by the present invention can resist heavy traffic load disturbances, and its excellent flexural tensile and bonding properties are of great significance to improving the service life of concrete bridges.

[0135] In summary, the anti-disturbance micro-expansion lightweight ultra-high performance concrete of the present invention has the properties of high anti-disturbance, high fluidity, high toughness, good volume stability, strong bonding performance and reasonable construction operation time, and therefore has important practical application value. It has a wide range of applications. When applied to the repair, reinforcement and widening of bridges, roads and other projects, it can not only carry out large-scale uninterrupted traffic construction and effectively relieve traffic pressure, but also effectively reduce the deadweight of the concrete structure and reduce the pressure on the original bridge bearing capacity. At the same time, it solves the problem of high fluidity and high anti-disturbance performance of concrete, and has important guiding significance for the development and promotion of lightweight ultra-high performance concrete.

[0136] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0137] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A disturbance-resistant micro-expansion lightweight ultra-high performance concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 35-40 parts of cement, 5-7 parts of fly ash microbeads, 6-9 parts of silica fume, 0.9-1.5 parts of whiskers, 0.05-0.10 parts of nanocellulose, 18-25 parts of spherical coal gangue ceramsite, 5-10 parts of crushed coal gangue ceramsite, 2.2-3.3 parts of expansion agent, 0.04-0.09 parts of temperature shrinkage notched fiber, 6.0-6.8 parts of steel fiber, 1.1-1.5 parts of water reducer and 7.0-9.2 parts of water.

2. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The fly ash microbeads have a ignition loss of ≤3.0%, a water requirement ratio of ≤90%, and a spherical particle volume ratio of ≥95%.

3. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The silica fume has a SiO2 mass content of ≥95% and a specific surface area of ​​≥19500m 2 / kg, 28d activity index ≥100%.

4. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The spherical coal gangue ceramsite and the crushed stone coal gangue ceramsite are continuously graded from 0.075 to 4.75 mm; The spherical gangue ceramsite and the crushed stone gangue ceramsite have a fineness modulus of 3.1 to 3.7, a cylinder pressure strength of ≥12.0 MPa, and a bulk density of 700 to 900 kg / m 3 , apparent density is 1500~1700kg / m 3 , saturated surface dry water absorption rate is 12.0%~14.0%.

5. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The whisker is one of silicon carbide whisker, calcium sulfate whisker and calcium carbonate whisker; The whisker has a diameter of 0.1 to 2 μm, a length of 10 to 30 μm, and a specific surface area of ​​20 to 80 m 2 / kg.

6. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The nanocellulose is cellulose nanofibers; The cellulose nanofibers are 1 to 10 μm long, 10 to 60 nm in diameter, and have a specific surface area of ​​100 to 130 m 2 / kg.

7. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylate-based high-efficiency water reducing agent.

8. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The specific surface area of ​​the expansion agent is ≥250m 2 / kg, 7d expansion rate limited to ≥0.035%.

9. The anti-disturbance micro-expansion lightweight ultra-high performance concrete according to claim 1, characterized in that: The shrinkage rate of the temperature-shrinkage notched fiber is 0.5-12%, the response temperature is 30-100° C., the tensile strength is 500-1500 MPa, and the elastic modulus is 7-30 GPa.

10. A method for preparing the anti-disturbance micro-expansion lightweight ultra-high performance concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix 18 to 25 parts by weight of spherical gangue ceramsite and 5 to 10 parts by weight of crushed stone-shaped gangue ceramsite to obtain gangue ceramsite; add water to the gangue ceramsite, stir evenly to make the gangue ceramsite fully pre-wet, cover and place in a cool and dry place to stand, and obtain saturated pre-wetted gangue ceramsite; wherein the mass of water is 12 to 14% of the mass of the gangue ceramsite; S2, pouring 35-40 parts by weight of cement, 6-9 parts of silica fume, 5-7 parts of fly ash microspheres, 2.2-3.3 parts of expansion agent, and 0.9-1.5 parts of whisker into a mixer and mixing to obtain a premix; S3, pouring the saturated pre-wetted coal gangue ceramsite in S1 into the premix, stirring to obtain a mixture; S4, adding 0.05-0.10 parts by weight of nanocellulose and 1.1-1.5 parts of a water reducing agent to 7.0-9.2 parts of water, stirring evenly, pouring into the mixture of S3, and stirring to obtain a mixed slurry; S5. 6.0 to 6.8 parts by weight of steel fiber and 0.04 to 0.09 parts by weight of temperature shrinkage notched fiber are uniformly added to the mixed slurry in S4, and molded after stirring. After covering with a film and curing, the mold is removed, and then standard curing or steam curing is performed to obtain the disturbance-resistant micro-expansion lightweight ultra-high performance concrete.

Citation Information

Patent Citations

  • Fiber-reinforced combined light aggregate concrete for structures

    CN104961396A

  • Full-scale fiber toughened ultra-high performance concrete and preparation method thereof

    CN111792890A

  • Steel fiber cement-based composite material based on nanoscale reinforcement and preparation method thereof

    CN113072343A

  • Ecological impact-resistant ultra-high performance concrete and application thereof

    CN113683361A

  • Temperature shrinkage induced anti-crack fiber and preparation method thereof

    CN116332541A

Cited By

  • High-disturbance-resistance cement-based material and preparation method thereof

    CN120757351A

  • A highly robust cementitious material and method of making the same

    CN120757351B

  • Thermal shrinkage type fiber reinforced cement-based material as well as preparation method and application thereof

    CN122127114A

  • Low-shrinkage high-toughness UHPC (Ultra High Performance Concrete) and impact property testing method thereof

    CN122520388A